Design and Implementation of Marker-Based Augmented Reality to Enhance Public Awareness in Waste - Sarah Faradilla; Caraka Aji Pranata (Journal of Applied Informatics and Computing, 2026)
Waste problem in Indonesia remains a complex issue for the community due to a low level of understanding and awareness about waste management and its impacts. On this research, we will aims to raise awareness and educate ranging from children, teenagers, to adults, about waste management using an Augmented Reality-based application that employs System Development Life Cycle method and evaluates the performance of Marker-Based Augmented Reality. Performance evaluation was conducted by testing the response time of marker recognition based on estimated distance and angle under normal and dim light intensity, as well as in outdoor lighting conditions. High-contrast visual markers with simple geometries were deliberately selected to maximize tracking stability. The test results showed that the system was able to recognize markers with an average response time of 0.31–0.93 seconds, which excellently meets the standard real-time AR response benchmark of under 1.0 second. Based on user assessment results through questionnaires distributed to 30 respondents and evaluated using the System Usability Scale method, the application received a perfect rating. Furthermore, preliminary pre-test and post-test evaluations indicated a significant improvement in users' comprehension when compared to conventional text-based educational methods, making it suitable for use as an interactive educational medium.